INVESTIGATING THE LEVEL OF NEWSPAPER AND MAGAZINE READING HABITS AMONG FACULTY MEMBERS OF FIRST GRADE COLLEGES IN CHIKMAGALUR - ShivaKumara , A S; Dharani , Kumar P (Current Journal of Library and Information Sciences (CJLIS), 2023)
The habit of reading newspapers and magazines provides a great sense of educational value and completeness as it offers information about various fields such as politics, education, sports, economy, entertainment, business, trade, and commerce. This study aims to investigate the level of newspaper and magazine reading habits among faculty members of first grade colleges in Chikmagalur. A survey method was used, and a self-developed questionnaire was administered to 286 respondents, of which 261 responses were received, representing a response rate of 91.26%. The findings revealed that a majority of the respondents read newspapers daily. The importance of reading newspapers and magazines cannot be overemphasized, as they play a vital role in providing information on recent issues, events, or happenings locally, nationally, and internationally. They contribute to the development of knowledge and provide valuable critical and commentary articles on socio-economic issues in current society. Reading newspapers has also been associated with improvement in students’ attitudes toward reading overall, and they provide accurate and current information for academic pursuits. The present study highlights the effects of newspapers and magazines on the academic pursuit of faculty members in first grade colleges in Chikmagalur.